Influence of electron - phonon interaction on piezoresistance of single crystals n-Ge - luniov, sergiy; Burban, Olexandr; Nazarchuk, Petro; Zimych, Andriy (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Piezoresistance of uniaxially deformed along the crystallographic direction [100] single crystals n-Ge< for different fixed temperatures has been investigated. Presence of the significant piezoresistance for given conditions of the experiment is explained by increase in the effective mass and decrease in the relaxation time for electrons at the expense of the inversion of (L1-†1) type of an absolute minimum in n-Ge. Temperature dependencies of resistivity for undeformed (L1model of conduction band) and deformed under uniaxial pressureP=3 GPÐ° (âˆ†1model of conduction band) single crystals n-Ge are obtained. Resistivity for undeformed single crystals n-Ge is changed according to the law Ï~T1.66. Resistivity for uniaxially deformed single crystals n-Ge is changed as Ï~T 1.53. The given dependencies show that for L1 model of the conduction band in contrast to ˆ†1model one must equally with intravalley scattering of electrons on acoustic phonons take into account scattering of electrons on optical and intervalley phonons. Therefore reduction of the magnitude piezoresistance n-Ge with the increasing temperature is associated with turning-off at the expense of the inversion of (L1-Î”1) type of absolute minimum under uniaxial pressure P>2.7 GPÐ° mechanism for scattering of electrons on intervalley and optical phonons. Comparison of results of theoretical calculations with relevant experimental data shows that peculiarities of piezoresistance n-Ge under uniaxial pressures 1.6<P<2.7 GPÐ° for (L1-Î”1) model of conduction band n-Ge can be described only taking into account nonequivalent intervalley scattering of electrons between the minima L1 andÎ”1. /em>